(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Karim HA, Najib NN, Ayu SM, Fidel. 2023. Characteristics of Maleo bird spawning nests (Macrocephalon maleo) in Lake Towuti, South Sulawesi.Biodiversitas 24: 670-676. Maleo birds (Macrocephalon maleo) have a habitat in the forest near the beach or in the middle of the forest near the hot springs. However, in Pekaloa Village, East Luwu District, Maleo birds are found in Lake Towuti, South Sulawesi, Indonesia. This, of course, shows that the habitat of Maleo birds on the shore of the lake is new information, especially on the island of Sulawesi. This research was conducted in Pekaloa Village, Towuti Sub-district, East Luwu District, South Sulawesi. This study was conducted to collect data on the characteristics of Maleo Senkawor (Macrocephalon maleo) nests. Secondary data collection began from scientific journals and works, as well as discussions with the surrounding community and the TWA manager of Lake Towuti, while primary data was obtained from measurements and direct observation in the field, as well as laboratory analysis. In this study, five nest plots with 13 nest holes were used, and the vegetation analysis used example plots measuring 175 m2. The characteristics of the nest pit have an average depth of 0.6 m, a surface diameter of 0.41 m, a temperature of 33.6oC, and a pH of 6.2. Vegetation analysis found eight species around the Maleo Senkawor bird’s nest. Vegetation analysis used the density formula: highest frequency density 19.5 and highest frequency 0.57, lowest density 0.02 and lowest frequency 0.14. This study forms the basis of new information in the conservation of Maleo birds with the characteristics of the habitat conditions for nesting Maleo birds, especially in the coastal area of the lake.